Rereading Russell : Essays on Bertrand Russell's Metaphysics and Epistemology. - Savage, C. Wade (Minnesota studies in the philosophy of science., 1989)
Rereading Russell was first published in 1989. Though Betrand Russell is best known for his formative role in the creation of symbolic logic (the Principia Mathematica) and analytic philosophy, he was also among the founders of twentieth-century philosophy of science; he used his method of logical analysis to devise a metaphysics and epistemology that could accommodate revolutionary changes in physics and psychology. Yet these areas -- especially in his later work -- have been neglected and undervalued. The essays in Rereading Russell help to remedy that neglect, by calling attention to the wh.